Nutrition: Boring Food - Donna Davis; Linda Bobroff (EDIS)
FAR-7000, a 2-page transcript of the radio broadcast by Donna Davis and Linda Bobroff, explains to parents why neither the rules they learned as kids nor the new rules coming from the diet industry are appropriate for feeding their children, and describes a more appropriate feeding philosophy advocated by Ellyn Satter. Includes links to sounds files of the radio broadcast. Published by the UF Department of Family Youth and Community Sciences, May 2006.